2017
DOI: 10.2337/dc17-0078
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Improves Left Ventricular Diastolic Function in Subjects With Diabetes

Abstract: OBJECTIVETo examine the effect of pioglitazone on myocardial insulin sensitivity and left ventricular (LV) function in patients with type 2 diabetes (T2D).RESEARCH DESIGN AND METHODSTwelve subjects with T2D and 12 with normal glucose tolerance received a euglycemic insulin clamp. Myocardial glucose uptake (MGU) and myocardial perfusion were measured with [18F]fluoro-2-deoxy-d-glucose and [15O]H2O positron emission tomography before and after 24 weeks of pioglitazone treatment. Myocardial function and transmitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 42 publications
1
51
0
3
Order By: Relevance
“…Whereas pioglitazone is associated with reduced cardiovascular risk, because undiagnosed diastolic dysfunction is more common in patients with NAFLD or T2DM, fluid retention that occurs during pioglitazone therapy may induce congestive cardiac failure and so is contraindicated in these patients. In patients without clinically evident cardiovascular disease, a small recent study found that pioglitazone was associated with improved left ventricular systolic and diastolic function …”
Section: Modulation Of Ir In Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas pioglitazone is associated with reduced cardiovascular risk, because undiagnosed diastolic dysfunction is more common in patients with NAFLD or T2DM, fluid retention that occurs during pioglitazone therapy may induce congestive cardiac failure and so is contraindicated in these patients. In patients without clinically evident cardiovascular disease, a small recent study found that pioglitazone was associated with improved left ventricular systolic and diastolic function …”
Section: Modulation Of Ir In Nafldmentioning
confidence: 99%
“…In patients without clinically evident cardiovascular disease, a small recent study found that pioglitazone was associated with improved left ventricular systolic and diastolic function. (30) Pioglitazone is associated with an increased risk of bone fractures. (31) A recent meta-analysis has reported that out of 26 studies, only five showed an association between bladder cancer and pioglitazone, (32) with no significant association found after exclusion of studies deemed to be of low quality.…”
Section: Peroxisome Proliferator-activated Receptor Gamma Agonistsmentioning
confidence: 99%
“…Thus, although fluid retention can occur in 5% to 10% of glitazone‐treated T2DM patients, less than 1% will develop HF. Moreover, a recent small clinical study using sophisticated measurement of heart function has suggested that pioglitazone can improve myocardial insulin sensitivity, LV diastolic function and systolic function in T2D . Improved myocardial insulin sensitivity and diastolic function are strongly correlated …”
Section: Safety Considerations: Balance Between Risk and Benefitmentioning
confidence: 99%
“…Moreover, a recent small clinical study using sophisticated measurement of heart function has suggested that pioglitazone can improve myocardial insulin sensitivity, LV diastolic function and systolic function in T2D. 96 Improved myocardial insulin sensitivity and diastolic function are strongly correlated. 96 Weight gain is the most common adverse effect associated with the use of glitazones because of fluid retention and increased adiposity.…”
Section: Safety Considerations: Balance Between Risk and Benefitmentioning
confidence: 99%
See 1 more Smart Citation